Dopant-free F-substituted benzodithiophene copolymer hole-transporting materials for efficient and stable perovskite solar cells. Issue 4 (3rd January 2020) - Kong, Xiangyu; Jiang, Yue; Wu, Xiayan; Chen, Cong; Guo, Jiali; Liu, Shengjian; Gao, Xingsen; Zhou, Guofu; Liu, Jun-Ming; Kempa, Krzysztof; Gao, Jinwei
Abstract : Perovskite solar cells based on dopant-free PBDT[2F]T have achieved a power conversion efficiency (17.52%), combined with an impressive stability in contrast to that with the doped spiro-OMeTAD as a HTM in ambient atmosphere and even in high humidity. Abstract : Polymeric hole-transporting materials (HTMs) with low production cost and versatile wet processing procedures are important for efficient and stable perovskite solar cells. In this study, three F-substituted benzodithiophene copolymers were introduced in perovskite solar cells as dopant-free efficient HTMs. Among them, perovskite solar cells based on dopant-free PBDT[2F]T achieved a comparable power conversion efficiency (PCE) (17.52%) to that of the well-known p-type doped spiro-OMeTAD (∼20.2%). More importantly, the solar cells with pristine PBDT[2F]T HTMs presented impressive stability in contrast to that with doped spiro-OMeTAD as the HTM in ambient atmosphere and even in high humidity. The detailed study showed that the dopant-free PBDT[2F]T HTM presents exceptional ability to extract holes from the perovskite layer, and simultaneously the capability to reduce trap-assisted recombination at the interface of perovskite/PBDT[2F]T. These findings pave the way for the development of dopant-free polymeric HTMs for the fabrication of cost-effective and stable perovskite solar cells.